The Effect of Consuming Food Allergens on Immune System Function with the Focus on Infectious Lung Diseases - Mohammad Kamalinejad; Razieh Nabimeybodi; Rahele Zareshahi; Naeemeh Nabimeybodi (Tehran University of Medical Sciences, 2021)
The pandemics of respiratory diseases are the most common ones comparing to other diseases. The latest pandemic is caused by COVID-19, for which no definitive cure has been found. Therefore, at present, strengthening the immune system is the only way to protect humans against this virus. Food is one of the factors assisting the immune system to function properly. Moreover, food plays an important role in strengthening the immune system against various pathogens. However, many popular sources of human food including legumes, eggs, and nuts contain substances called anti-nutritional factors that can adversely affect the human immune system and increase inflammatory factors such as interleukin 4 and interleukin 6. A cytokine storm and increased secretion of interleukin 4 and 6 are among the most frequent causes of death in COVID-19 patients. Consequently, taking the COVID-19 patient's diets into account by considering the foods influencing their immune system can greatly reduce the severity of the disease and its mortality rate.